Precision irrigation management: An innovative technique for efficient water management - Verma, Sandeep Kumar; Verma, Aparna (Indian Farming, 2023)
Irrigation is the artificial application of watering the crops for their survival, growth and development. The need of irrigation for crop production is increasing due to rise in drought indices and quick population growth. Yet, there are a number of problems that irrigated agriculture needs to grapple with, which have led to subpar performance, wasteful water use and low water output. In order to make up for the short-comings of rainfall, freshwater is necessary for irrigation and the supply of nutrients for plant growth. Over 70% of the fresh water resources are used for agricultural purposes. The traditional approach of managing irrigation has issues including low water use efficiency and low production. Using a precision irrigation management technique that reduces water losses, balances supply and demand, and tracks performance is necessary to increase the efficiency of water used in crop production. It also handles the variability of land in terms of water stress through variable rate irrigation.